A potted history of freshwater management in New Zealand - Knight, Catherine (New Zealand Science Review, 2022)
This article traces the history of freshwater management in New Zealand from the earliest laws to protect newly introduced trout and salmon from pollution in the 1860s through to what an increasing number of New Zealanders today consider as a ‘freshwater crisis’ – a consequence of the failure of government to respond adequately to the unprecedented speed and scale of land use intensification and its impacts over the last few decades. Two themes are highlighted by this history: the tension between the protection and use of our water (and land) resources; and the tendency of government to intervene only when serious environmental damage has become evident.